1983
DOI: 10.1093/infdis/148.6.1069
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of Gentamicin in Purulent Sputum from Patients with Cystic Fibrosis or Bronchiectasis: Comparison with Activity in Serum

Abstract: Two mechanisms of potential biologic antagonism of gentamicin in purulent sputum from patients with cystic fibrosis or bronchiectasis were studied: reduction of activity by ions and antibiotic binding. Antagonism by ions was assessed by examination of the activity of gentamicin against Pseudomonas aeruginosa in dialysates of serum or sputum in ion-depleted broth. The ionic content of the dialysates increased and reflected differences in the ion content of serum and sputum. Gentamicin had significantly less act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 20 publications
1
50
0
1
Order By: Relevance
“…We were motivated by the fact that CF sputum is known to inactivate aminoglycosides through binding and antagonism by cations, (8,9) so that in vitro studies of dialysates of CF sputum showed bioactive drug concentrations to be 10-25-fold lower than total drug concentrations. (10,11) In our study, bioactive peak concentrations were on average 66% lower than total peak concentrations, corroborating the prior in vitro observations though with a smaller magnitude of sputum inactivation. Bioactive and total trough concentrations in respiratory secretions were similar, suggesting that sputum inactivation of aminoglycosides may be concentrationdependent, occurring to a greater extent at higher concentrations.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…We were motivated by the fact that CF sputum is known to inactivate aminoglycosides through binding and antagonism by cations, (8,9) so that in vitro studies of dialysates of CF sputum showed bioactive drug concentrations to be 10-25-fold lower than total drug concentrations. (10,11) In our study, bioactive peak concentrations were on average 66% lower than total peak concentrations, corroborating the prior in vitro observations though with a smaller magnitude of sputum inactivation. Bioactive and total trough concentrations in respiratory secretions were similar, suggesting that sputum inactivation of aminoglycosides may be concentrationdependent, occurring to a greater extent at higher concentrations.…”
supporting
confidence: 91%
“…(8,9) In vitro investigations have suggested that bioactive tobramycin concentrations may be 10-25-fold lower than total drug concentrations in CF sputum. (10,11) Prior pharmacokinetic studies have measured tobramycin concentrations in CF sputum only by chemical means [immunoassay or highpressure liquid chromatography (HPLC)]. (3)(4)(5)12) In the current study, measurement of sputum tobramycin concentrations by bioassay (13) as well as HPLC allowed, for the first time, a comparison of bioactive and total tobramycin concentrations in respiratory secretions.…”
mentioning
confidence: 88%
“…Moreover, like bovine DNase I, rhDNase is inactivated by heat (100°C for 10 min), is specifically inhibited by actin (using a 1:1 molar ratio ofrhDNase and rabbit muscle actin), and shows optimal enzymatic activity at neutral pH (5.5-7.5) (39). Both the reported concentrations of Ca2+ and Mg2+ in sputum and the pH of sputum are sufficient to support the activity of rhDNase (40,41).…”
Section: Resultsmentioning
confidence: 90%
“…The metals tested were 100 M Fe(NH 4 ) 2 (SO 4 ) 2 [containing 100 M Fe(II), as determined by weight and the ferrozine assay], 100 M FeCl 3 , 5 mM CaCl 2 , 100 M MnCl 2 , 10 mM MgCl 2 , 100 M ZnCl 2 , and 100 M CuCl 2 . The concentrations of calcium and magnesium were selected to approximate physiologically relevant concentrations (27).…”
Section: Methodsmentioning
confidence: 99%